Effective Advertising Location in the Commuter Line: Study Cases in Jakarta and Surrounded Cities in Indonesia - Levyda Levyda; Tri Nur Ismi (The Winners, 2020)
The aims of the research were to determine the most effective advertising location compared to various available locations and to examine the behavior of commuter line passengers. The research was conducted at six train stations and samples were taken by a purposive sampling method. Data were collected by a structured interview. The Chi-square test was used to find out the differences of the advertising locations’ effectiveness, while a ranking method was used to determine the effectiveness of advertising locations. Eight locations were rated by passengers. The results reveal that the effectiveness of each location on the commuter line has proven to be different and the most effective advertising location is the hanging alley.